2008
DOI: 10.1111/j.1439-0523.2008.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

The action of three Beet yellows virus resistance QTLs depends on alleles at a novel genetic locus that controls symptom development

Abstract: Beet yellows virus (BYV) can dramatically reduce yield from sugar beet crops. A BYV resistant plant from a Beta germplasm accession was crossed with a sugar beet plant to generate the segregating population BYV1. This population was evaluated for BYV resistance and analysed with amplified fragment length polymorphism and singlenucleotide polymorphism markers to identify resistance loci. At 2 weeks after inoculation a number of plants displayed either mosaic or vein-clearing disease symptoms on infected leaves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…An important technique that has improved the efficiency of selection in numerous crops is marker-assisted selection (MAS). Numerous studies have identified markers associated with traits in sugar beet including root elongation and glucose and fructose content (Stevanato et al, 2010), sucrose content and quality (Schneider et al, 2002), cytoplasmic male sterility (CMS) (Hjerdin-Panagopoulos et al, 2002;Honma et al, 2014;Moritani et al, 2013), post-winter bolting resistance (Pfeiffer et al, 2014), yield (Schwegler et al, 2014), and resistances to beet diseases including: Rhizomania (Beet Necrotic Yellow Vein Virus; BNYVV) (Barzen et al, 1997;Gidner et al, 2005;Grimmer et al, 2007a;Lein et al, 2007;Scholten et al, 1999), beet yellows virus (BYV) (Grimmer et al, 2008), powdery mildew (Erysiphe polygoni DC.) (Grimmer et al, 2007b;Janssen et al, 2003), Aphanomyces root rot (Aphanomyces cochlioides Drechsler) (Taguchi et al, 2009(Taguchi et al, , 2010, root-knot nematode (Meloidogyne spp.)…”
Section: Core Ideasmentioning
confidence: 99%
“…An important technique that has improved the efficiency of selection in numerous crops is marker-assisted selection (MAS). Numerous studies have identified markers associated with traits in sugar beet including root elongation and glucose and fructose content (Stevanato et al, 2010), sucrose content and quality (Schneider et al, 2002), cytoplasmic male sterility (CMS) (Hjerdin-Panagopoulos et al, 2002;Honma et al, 2014;Moritani et al, 2013), post-winter bolting resistance (Pfeiffer et al, 2014), yield (Schwegler et al, 2014), and resistances to beet diseases including: Rhizomania (Beet Necrotic Yellow Vein Virus; BNYVV) (Barzen et al, 1997;Gidner et al, 2005;Grimmer et al, 2007a;Lein et al, 2007;Scholten et al, 1999), beet yellows virus (BYV) (Grimmer et al, 2008), powdery mildew (Erysiphe polygoni DC.) (Grimmer et al, 2007b;Janssen et al, 2003), Aphanomyces root rot (Aphanomyces cochlioides Drechsler) (Taguchi et al, 2009(Taguchi et al, , 2010, root-knot nematode (Meloidogyne spp.)…”
Section: Core Ideasmentioning
confidence: 99%
“…Anchoring of linkage groups to specific sugar beet chromosomes was achieved by identification of common, dominant AFLP marker alleles with previous populations (Grimmer et al ., 2007a,b; Grimmer et al ., 2008; unpublished data) and by the inclusion of previously published SNP markers in the 06‐158 BC 1 (BNYVV test) population. Informative dominant AFLP marker alleles for anchoring of linkage groups with previously published groups containing SNP markers were EAGA/MACT‐246 (Grimmer et al ., 2008), EAGC/MATA‐67 and EAGA/MCAA‐77 (Grimmer et al ., 2007a). The latter marker allele was referred to as EAGA/MCAA‐76 in the previous publication.…”
Section: Resultsmentioning
confidence: 99%
“…The exception is that of rhizomania resistance (Giorio et al 1997;Scholten and Lange 2000;Gidner et al 2005;Grimmer et al 2008;Amiri et al 2009). Rhizomania (crazy root) severely impacts yield and has worldwide economic importance.…”
Section: Present Situationmentioning
confidence: 96%
“…sucrose percentage), or the traits are subject to non-additive variation (e.g. root yield), that is, the combination of genes and alleles and their interactions may be more important than the state of the genes themselves (Schafer-Pregl et al 1999;Nilsson et al 1999;Setiawan et al 2000;HjerdinPanagopoulos et al 2002;Schneider et al 2002;Lein et al 2007;Grimmer et al 2008;Stevanato et al 2010;Taguchi et al 2010). This is where molecular markers can be used to gain clarity into the quantitative genetic contributions (e.g., quantitative trait loci, QTLs) as well as provide some context in which they can be deployed effectively, prior to applying markers for assisted selection.…”
Section: Present Situationmentioning
confidence: 98%